Pemberdayaan Masyarakat dalam Rehabilitasi Hutan dan Lahan melalui Program Kebun Bibit Rakyat di Desa Sumberrejo Kecamatan Tempel Kabupaten Sleman - Wibawa, Aris (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2014)
The problem of critical and less productive land in Sumberrejo village, Tempel sub district,Â  Sleman district is chosen as the research location because it is adjacent to the Krasak river, which also support the quality and function of its subÂ  river basin (sub DAS). This research uses the combination of qualitative and quantitative methods. The result shows that the form of effort in the community enpowerment which is done in the KBR programme is able to increase the farmer group capacity especially at the aspects of technique, institute, administration and entrepreneur. The society participation at the planning step for the programme planning is at the informing level and the planning of activity implementation is at the delegated power level and consultation level for the policy maker. At the action step for the power mobilization is at the delegated power level and problem solving is at the consultation level. The evaluation step with monitoring variable at the partnership level and evaluation is at the consultation level. The planting successfulness level with realization of the wide planting area and the realization of planting growth is in the criteria success. The KBR programme implies in increasing potency of the society welfare.